Potential production and spatial distribution of hybrid poplar as a biofuel crop in Connecticut, USA - Xue, Zhao; Qu, Liqin; Yang, Xiusheng (International Journal of Agricultural and Biological Engineering, 2014)
The objective of this study was to assess the biomass production potential from hybrid poplars using marginal lands in the state of Connecticut, USA. A land-use suitability model was developed to identify and classify marginal lands in the state that could be used for growing hybrid poplars as a biofuel woody energy crop. The model was built on a geographic information system (GIS) platform, consisting of an exclusion area section, an ecological suitability section, and an economic/land-use suitability section. The model then was used to estimate the total biomass of the land-cover forests, annual biomass from forest and agricultural residues, and in particular the production potential of biomass from hybrid poplars over marginal lands in the state at county level. The results indicated that about 50% of the land in this state is unavailable for hybrid poplar cultivation and that less than 5% is highly suitable. The amount of usable area is highly variable on the county level. Without large-scale land use change, it appears that biofuel production in this state can only be a supplemental resource to the current energy supply.Keywords: biofuel plants, hybrid poplar, suitability model, spatial distribution, ethanol production, Connecticut, ecological suitabilityDOI: 10.3965/j.ijabe.20140702.002Citation: Xue Z, Qu L Q, Yang X S. Potential production and spatial distribution of hybrid poplar as a biofuel crop in Connecticut, USA. Int J Agric & Biol Eng, 2014; 7(2): 10－18.